2020
DOI: 10.1101/2020.02.17.952986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autonomic arousal tracks outcome salience not valence in monkeys making social decisions

Abstract: The evolutionary and neural underpinnings of human prosociality are still largely unknown. A growing body of evidence suggests that some species find the sight of another individual receiving a reward reinforcing, often called vicarious reinforcement. One hypothesis is that vicarious reward is reinforcing because it is arousing like a primary reward. We evaluated this hypothesis by measuring the autonomic pupil response of eight monkeys across two laboratories in two different versions of a vicarious reinforce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In intact (i.e., unoperated) monkeys, preference for Other is dependent on the presence of the partner monkey; baseline prosocial preferences are absent in the Nonsocial condition [30]. In the Nonsocial sessions of the retention test of this study, only one monkey (C3) showed a numerical preference for giving juice to the collection jar, but this was not significant (S2 Fig; t 19 = 0.87, p = 0.398).…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…In intact (i.e., unoperated) monkeys, preference for Other is dependent on the presence of the partner monkey; baseline prosocial preferences are absent in the Nonsocial condition [30]. In the Nonsocial sessions of the retention test of this study, only one monkey (C3) showed a numerical preference for giving juice to the collection jar, but this was not significant (S2 Fig; t 19 = 0.87, p = 0.398).…”
Section: Resultsmentioning
confidence: 60%
“…Preoperatively, all 6 actor monkeys showed a reliable prosocial preference for Other trials over Neither trials [30], and the magnitude of this preference did not differ between the groups designated to serve as controls or receive surgery (Fig 2A; t 3 = 0.37, p = 0.735).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations